IMPLEMENTASI TERHADAP PEMENUHAN HAK-HAK ANAK DALAM MEMPEROLEH PENDIDIKAN YANG LAYAK BERDASARKAN PERATURAN PEMERINTAH NO. 47 TAHUN 2008 - MAISAROH OKTAVIANI KHAIRULLAH (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT        Education is one of the tools to transform human character. With education, people can find out everything that is not or has not been previously known. Education is important in human life. Education, skills, knowledge is one of the capital that we have to live in this difficult times.But in terms of implementation, not all programs and regulations are implemented on target and as mandated by the government. Secondly, in terms of the public are still many children of school age to school should not even go to school, and there are some who prefer to work. Factors mentality and social environment affect children's motivation to fulfill its obligations in the following compulsory education.In the theory of government, the principal task of government, namely: service, empowerment, and construction. In the view in terms of the role, the government's success in carrying out its duties and functions, must be measured by these three functions. Keywords: children's rights, decent education